Comparative study of salt tolerance between two soybean varieties (Glycine max. L) at germination stage - Afrin, Sadia; Hossain, Feroza; Halim, Md Abdul; Akhtar, Nahid (Jahangirnagar University Journal of Biological Sciences, 2024)
In December 2019, a research work on seed germination was carried out in Plant Physiology and Biochemistry Laboratory, Jahangirnagar University, to determine the salt tolerance level and compare the salt stress response between two soybean varieties at early seedling stage. Seeds of soybean varieties viz Shohag and BARI Soybean-5 were grown in Petri dishes and treated with 0, 50, 100, 150, 200, 250, and 300 mM NaCl for 14 days. Salinity had adverse effects on germination percentage, germination index, germination speed and growth parameters viz shoot length, root length, fresh weight of shoots, fresh weight of roots and dry matter production in shoot and root for early seedling growth. The results illustrate that germination percentage and germination index of Shohag were more than 80% at up to 200 mM NaCl concentration, while both of these variables for BARI Soybean-5 were more than 80% at up to 100 mM NaCl treatments. Although the germination speed of BARI Soybean-5 was faster than Shohag at moderate salinities, it was much slower for BARI Soybean-5 than Shohag at high salinities. Results showed that the growth of both varieties slowed significantly with increased salinity. However, Shohag outperforms BARI Soybean-5 in terms of growth at high salt concentration. As a result, it can be stated that BARI Soybean-5 can tolerate moderate salt. It can be hypothesized that Shohag could be used for field experiments due to its superior germination performance. Jahangirnagar University J. Biol. Sci. 12(1 & 2): 35-44, 2023 (June & December)